Expedient preparative isolation, quantification and characterization of limonoids from neem fruits - Haldar, Saikat; Phapale, Prasad B.; Kolet, Swati P.; Thulasiram, Hirekodathakallu V. (Analytical Methods, 2013)
Major basic limonoids from Neem fruits such as azadirone, epoxyazadiradione and azadiradione were isolated in preparative scale using an automated and rapid medium pressure liquid chromatography (MPLC)-based protocol. They were individually quantified using HPLC. An LC-ESI-MS/MS-based rapid identification technique was developed for the high-throughput screening of these limonoids in phytochemical extracts.

Expedient preparative isolation and tandem mass spectrometric characterization of C-seco triterpenoids from neem oil - Haldar, Saikat; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Dandekar, Devdutta S.; Thulasiram, Hirekodathakallu V. (Journal of Chromatography A, 2014)
C-seco triterpenoids are widely bioactive class of natural products with high structural complexity and diversity. The preparative isolation of these molecules with high purity is greatly desirable, although restricted due to the complexity of natural extracts. In this article we have demonstrated a Medium Pressure Liquid Chromatography (MPLC) based protocol for the isolation of eight major C-seco triterpenoids of salannin skeleton from Neem (Azadirachta indica) oil. Successive application of normal phase pre-packed silica-gel columns for the fractionation followed by reverse phase in automated MPLC system expedited the process and furnished highly pure metabolites. Furthermore, eight isolated triterpenoids along with five semi-synthesized derivatives were characterized using ultra performance liquid chromatography-electrospray ionization-quadrupole/orbitrap-MS/MS spectrometry as a rapid and sensitive identification technique. The structure-fragment relationships were established on the basis of plausible mechanistic pathway for the generation of daughter ions. The MS/MS spectral information of the triterpenoids was further utilized for the identification of studied molecules in the complex extract of stem and bark tissues from Neem. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ESI(+)-quadrupole/orbitrap-MS/MS; MPLC; Neem oil; Preparative isolation; Salannin; Triterpenoids

Engineering cell surface glycans with carbohydrate enantiomers to alter bacterial binding and adhesion - Gade, Madhuri; Chaudhary, Preeti Madhukar; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra (Chemistryselect, 2017)
Chirality of carbohydrate has critical functions in many biological processes. Changes in the configuration of even one sugar molecules may cause abnormal behavior or even inhibit specific processes. Herein, we have shown bioorthogonal conjugation of mannose enantiomers on HeLa cell surfaces induced a different rate of bacterial binding and cell adhesion.
Keywords: Bioorthogonal reaction; Carbohydrate; E. coli; Enantiomer; Surfaces functionalization

Exploring the influence of shapes and heterogeneity of glyco-gold nanoparticles on bacterial binding for preventing infections - Toraskar, Suraj; Gade, Madhuri; Sangabathuni, Sivakoti; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra (Chemmedchem, 2017)
To investigate the effects of the heterogeneity and shape of glyco-nanoprobes on carbohydrate-protein interactions (CPIs), alpha-d-mannose-and beta-d-galactose-linked homo-and heterogeneous glycodendrons were synthesized and immobilized on spherical and rod-shaped gold nanoparticles (AuNPs). Lectin and bacterial binding studies of these glyco-AuNPs clearly illustrate that multivalency and shape of AuNPs contribute significantly to CPIs than the heterogeneity of glycodendrons. Finally, bacterial infection of HeLa cells was effectively inhibited by the homogeneous glycodendron-conjugated rod-shaped AuNPs relative to their heterogeneous counterparts. Overall, these results provide insight into the role of AuNP shape and multivalency as potential factors to regulate CPIs.

Epoxyazadiradione suppresses breast tumor growth through mitochondrial depolarization and caspase-dependent apoptosis by targeting PI3K/Akt pathway - Kumar, Dhiraj; Haldar, Saikat; Gorain, Mahadeo; Kumar, Santosh; Mulani, Fayaj A.; Yadav, Amit S.; Miele, Lucio; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (BMC Cancer, 2018)
Background: Breast cancer is one of the most commonly diagnosed invasive cancers among women around the world. Among several subtypes, triple negative breast cancer (TNBC) is highly aggressive and chemoresistant. Treatment of TNBC patients has been challenging due to heterogeneity and devoid of well-defined molecular targets. Thus, identification of novel effective and selective agents against TNBC is essential. Methods: We used epoxyazadiradione to assess the cell viability, mitochondrial potential, ROS level, cell migration, apoptosis and protein expression in cell culture models of TNBC MDA-MB-231 and ER+MCF-7 breast cancer cells. The molecular mechanism was examined in two different type of breast cancer cells in response to epoxyazadiradione. We have also analyzed the effect of epoxyazadiradione on breast tumor growth using in vivo mice model. Results: In this study, we for the first time investigated that out of 10 major limonoids isolated from Azadirachta indica, epoxyazadiradione exhibits most potent anti-cancer activity in both TNBC and ER+breast cancer cells. Epoxyazadiradione induces apoptosis and inhibits PI3K/Akt-mediated mitochondrial potential, cell viability, migration and angiogenesis. It also inhibits the expression of pro-angiogenic and pro-metastatic genes such as Cox2, OPN, VEGF and MMP-9 in these cells. Furthermore, epoxyazadiradione attenuates PI3K/Akt- mediated AP-1 activation. Our in vivo data revealed that epoxyazadiradione suppresses breast tumor growth and angiogenesis in orthotopic NOD/SCID mice model. Conclusion: Our findings demonstrate that epoxyazadiradione inhibits PI3K/Akt-dependent mitochondrial depolarisation, induces apoptosis and attenuates cell migration, angiogenesis and breast tumor growth suggesting that this compound may act as a potent therapeutic agent for the management of breast cancer.
Keywords: Angiogenesis; Apoptosis; Breast cancer; Limonoids; Metastasis; PI3K